Pre-emptive pangenotypic direct acting antiviral therapy in donor HCV-positive to recipient HCV-negative heart transplantation: an open-label study. (October 2019) - Bethea, Emily D; Gaj, Kerry; Gustafson, Jenna L; Axtell, Andrea; Lebeis, Taylor; Schoenike, Mark; Turvey, Karen; Coglianese, Erin; Thomas, Sunu; Newton-Cheh, Christopher; Ibrahim, Nasrien; Carlson, William; et al.
Summary: Background: Low donor heart availability underscores the need to identify all potentially transplantable organs. We sought to determine whether pre-emptive administration of pangenotypic direct-acting antiviral therapy can safely prevent the development of chronic hepatitis C virus (HCV) infection in uninfected recipients of HCV-infected donor hearts. Methods: Patients were recruited for this an open-label, single-centre, proof-of-concept study from Nov 1, 2017, to Nov 30, 2018. Following enrolment, the recipient's status on the heart transplantation waiting list was updated to reflect a willingness to accept either an HCV-positive or HCV-negative heart donor. Patients who underwent transplantation with a viraemic donor heart, as determined by nucleic acid testing (NAT), received pre-emptive oral glecaprevir-pibrentasvir before transport to the operating room followed by an 8-week course of glecaprevir-pibrentasvir after transplantation. Patients receiving HCV antibody-positive donor hearts without detectable circulating HCV RNA were followed using a reactive approach and started glecaprevir-pibrentasvir only if they developed viraemia. The primary outcome was achievement of sustained virological response 12 weeks after completion of glecaprevir-pibrentasvir therapy (SVR12). Patients were followed from study enrolment to 1 year after transplantation. This is an interim analysis, initiated after all enrolled patients reached the primary outcome. Results reflect data from Nov 1, 2017, to May 30, 2019. This trial is registered withClinicalTrials.gov, numberNCT03208244 . Findings: 55 patients were assessed for eligibility and 52 consented to enrolment. 25 patients underwent heart transplantation with HCV-positive donor hearts (20 NAT-positive, five NAT-negative), three of whom underwent simultaneous heart–kidney transplantation. All 20 recipients of NAT-positive hearts tolerated glecaprevir-pibrentasvir and showed rapid viral suppression (median time to clearance 3·5 days, IQR 0·0–8·3), with the subsequent achievement of SVR12 by all 20. The five recipients of NAT-negative grafts did not become viraemic. Median pre-transplant waiting time for patients following enrolment in the HCV protocol was 20 days (IQR 8–57). Patient and allograft survival were 100% at a median follow-up of 10·7 months (range 6·5–18·0). Interpretation: Pre-emptive administration of glecaprevir-pibrentasvir therapy results in expedited organ transplantation, rapid HCV suppression, prevention of chronic HCV infection, and excellent early allograft function in patients receiving HCV-infected donor hearts. Long-term outcomes are not yet known. Funding: American Association for the Study of Liver Diseases, National Institutes of Health, and the Massachusetts General Hospital.